Phytoplankton ecology and hydrological dynamics of the yahuarcaca lake system, amazonas, colombia: integrated analysis of 16 years of study (2012)
This article provides a synthesis of the current knowledge on the evolving relation between the Amazon River and the Yahuarcaca lagoon system, through the limnological features and the ecology of phytoplankton in a period of sixteen years. The synthesis of the information was conducted by reviewing existing data about the system, for the time indicated, and analyzing it by means of descriptive statistics and linear correlation between the variables found. Also, it contains a summary of the most important aspects of the first attempt in Colombia to evaluate the influence of the flood pulse on the phytoplankton in a daily time scale. The thermal pattern of this laggon system corresponds to a warm and constant polymicthic lake type according to the de Lewis (1983) classification. The physical, chemical and biological variables examined in this várzea system change according to the hydrologic period. The conductivity, transparency and richness of the phytoplankton increase in the low water season, while the nutrient concentration, and the density, productivity and the biomass of phytoplankton increase during the high water season. Nitrate during the low water season and phosphate during the high water season are the most restricting nutrients. The changes that have taken place through these years in the connectivity between the river and the Yahuarcaca lagoon system are reflected in the dynamics of the structure and composition of the phytoplankton.